Pengaruh Motivasi Terhadap Kinerja Karyawan pada PT. Daeah E&C RDMP Balikpapan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of work motivation on employee performance at PT. Daeah E&C RDMP Balikpapan. This study is based on the importance of motivation as an internal factor that drives increased productivity and individual performance within an organization. This study uses a quantitative approach with a survey method and total sampling technique on the entire population of 40 employees. Data collection was conducted through Likert scale questionnaires, observations, and documentation. Data analysis utilized validity tests, reliability tests, classical assumption tests, and simple linear regression. The results of the study indicate that work motivation has a positive and significant impact on employee performance, with a significance value of 0.000 and a regression coefficient of 0.854. The implications of these findings suggest that enhancing motivation, both intrinsically and extrinsically, can improve employee performance. Therefore, companies are advised to develop integrated motivation strategies that incorporate other aspects such as leadership, organizational culture, and reward systems to create a productive and sustainable work environment.